Deutsche Flüchtlinge aus Ostpreußen in Dänemark 1945–1949 - Herzig, Elisa Mariélle (2023)
After the expulsion of East Prussian refugees to Denmark in 1945, the country had to adjust to taking in thousands of refugees within a very short time. Elisa Herzig sheds light on the fate of these people and paints a comprehensive picture of their challenges, everyday life, nutrition and schooling in the Danish camps. The author also looks at how the East Prussian refugees experienced their stay and treatment in a foreign country. Through extensive source work and the inclusion of eyewitness accounts and diaries, she succeeds in providing an in-depth analysis of this past refugee crisis, the conclusions of which are also highly relevant for the 21st century.